On the Question of Kitab Jawi’s Originality: Analysis on al-Fatani’s Nahj al-Raghibin on Essentials of Sale Contract - Buang, Ahmad Hidayat; Daud, Mohd Zaidi; Jamaludin, Mohd Hafiz (Afkar: Jurnal Akidah dan Pemikiran Islam, 2023)
Some scholars of Malay classics believe that Malay traditional religious books or Kitab Jawi, being a mere translation from Arabic sources, have little practical purposes outside the realm of beliefs, rituals, and family. Considering current commercial development, especially in Islamic banking and finance, the above claims need some qualifications, especially considering no further studies have been conducted to support their conclusion. This is especially so to determine the extent of the remarks made by the authors of Kitab Jawi in their texts whether merely a literal translation of the Arabic texts or containing some new and specific contributions worthwhile investigating. It is therefore the aim of this article to analyse the contents of these Kitab Jawi and compared them with the Arabic sources that they claimed to refer to. It is hoped that this analysis should provide an understanding of these Kitab Jawi can be considered original in respect of discussion and elaboration of translated texts. The analysis will focus on Shaykh Dawud’s work of Nahj al-Raghibin with special reference to the essentials of the sale contract. The selection of the subject of the sale contract is to demonstrate that the authors of Kitab Jawi had some appreciation on the trade and business prevailing during their compilation. The article argues that Nahj is not simply a translation of the Arabic texts, but it is an academic exercise, which consists of selecting, rearranging, and supplementing and presenting ideas and concepts of law.